Just Joking? investigating sexual harassment in a departmental store in Gweru, Zimbabwe - Hungwe, Chipo (UAS, 2016)
This study investigates the reasons for sexual harassment, its nature and policy implications in a departmental store in Gweru, Zimbabwe. It also analyses the costs of sexual harassment on both the individual and the organisation. The study is based on a qualitative research conducted between January and July 2008. 24 respondents (14 females and 10 males) were studied using semi structured interviews and questionnaires. Results are analysed using the Miles and Huberman (1994) approach to data analysis. Results reveal that contract employment and lack of skills create vulnerability and dependency, a situation exploited by the powerful male superiors who sexually harass their subordinate females. Sexual harassment is institutionalised at Tatenda where management refuses to acknowledge it as a problem. The reluctance of management to craft policies on sexual harassment and grievance procedures added to women’s fear of reporting sexual harassment perpetuates a culture of silence at Tatenda.